Spatio-Temporal Dynamics of Urban Green Space and Temperature in Ado-Ekiti Metropolis, Nigeria (2020)
The Nexus between the Urban Green Space (UGS) and Land Surface Temperature (LST) helps to formulate policy for sustainable management of UGS where there is an urban sprawl like Ado Ekiti. However, there is a dearth of information on UGS and LST in Ado-Ekiti. Therefore, this study adopted remote sensing and geographic information system techniques to determine the dynamics and nexus between UGS and LST as well as investigating the perceived factors responsible for the UGS changes in Ado-Ekiti metropolis, Nigeria with a view to providing relevant information for sustainable management of the UGS and mitigating the Urban Heat Island. Landsat imageries of 1987 (TM), 1998 (ETM) and 2019 (OLI) were obtained. Map of Ado-Ekiti was georeferenced and digitized to obtain its shapefile. The maximum likelihood algorithm of supervised classification in ArcGIS was used to classify Landsat imageries. The shapefile was superimposed on the classified imageries and clipped for the determination of land use land cover sizes. The LST was extracted from the imageries by converting the digital numbers to the surface temperature. Correlation analysis was used to determine the nexus between the UGS and LST. Four land use land cover: green spaces, built-up area, water bodies and bare land, were identified in the Ado-Ekiti metropolis. The UGS decreased from 74.4% in 1987 to 38.7% in 2019. Similarly, water bodies reduced from 0.9% in 1987 to 0.1% in 2019 respectively. However, built-up area and bare land increased from 21.9% and 2.9% in 1987 to 51.1% and 10.5% in 2019 respectively. The LST in Ado-Ekiti metropolis increased from 22.1°C in 1987 to 30.5 °C in 2019 respectively. The Built-up area and bare land had the highest LST values compared with UGS and water body in all the years. The relationship between the UGS dynamics and LST was negatively correlated with r2 ranging from -0.51 to -0.83. By the year 2049, the vegetation would have reduced to 36.0% while built-up and bare land would have increased to 52.4%. on the other hand, water with no significant change.